Nutrient Composition and Hypocholesterolemic Effect of black Seeds (Nigella Sativa L.) and its Oil - Al-Naqeeb, Ghanya Naji (2005)
Nigella sativa Linn. (Ranuculacea) popularly known as the black seed or Habbatus Sauda is a herb that has traditionally been used for centuries in many parts of the world. It has gained popularity due to its potential health benefits. This study was carried out to investigate the nutrient composition and in vivo hypocholesterolemic effect of the black seeds cultivated in Yemen and its oil. The nutrient composition of three different samples of Nigella sativa seeds from three different regions in Yemen, namely Marib, Sadah and Taiz were studied. Proximate analysis, total dietary fiber (TDF), insoluble dietary fiber (IDF) and soluble dietary fiber (SDF) were determined by the Association of Official Analytical Chemists methods (AOAC). Mineral analysis was carried out using Atomic Absorption spectrophotometer (AAS). Fatty acid methyl esters composition was determined using Gas Chromatography (GC), vitamin E (atocopherol) using HPLC and antioxidant activity by ferric thiocyanate (FTC) and thiobarbituric acid (TBA) methods. Results show that the three samples of Nigella sativa seeds have high content of fat which were 38.4 * 2.1, 37.7 * 0.1, and 36.8 * 1.4% in Sadah, Marib, and Taiz, respectively. In addition, Nigelln sativa seeds have a high content of TDF (36.88 1.44, 26.50 k 1.05, 30.40 * 1.06% for Marib, Sadah and Taiz samples, respectively), IDF (27.10 * 0.55, 20.56 * 1.16, 22.40 * 1.40 % for Marib, Sadah and Taiz samples, respectively) and SDF (8.90 & 1.17, 6.50 * 0.60, 8.13 + 0.71 % for Marib, Sadah and Taiz samples, respectively). Nigella sativa seeds are also rich in calcium, magnesium, potassium, phosphorus and iron. The major fatty acids in Nigella sativa oil extracts from n-hexane were oleic and linolenic which exist as unsaturated fatty acids. Palmitic, stearic and myristic acids were the main saturated fatty acids in all three samples. Oil extracted from the seeds showed higher antioxidant activity compared to a-tocopherol, and was rich in vitamin E (120 + 0.15, 170 k 0.40 and 290 + 1.5 mg/100g for Marib, Sadah and Taiz samples, respectively). The effect of Nigella sativa seed powder and its oil on hypercholesterolemia-induced rabbits was also studied for 8 weeks. A significant reduction (p< 0.05) of total cholesterol (TC) and low density lipoproteins (LDL) in Nigella sativa powder (NSP) and Nigella sativa oil (NSO) groups were observed at weeks 2, 4, 6 and 8. Treatment of rabbits with NSP and NSO showed a significant increase (p>0.05) in plasma HDL levels at weeks 4, 6 and 8 of treatment. A significant decreased (pc0.05) of malondialdehyde (MDA) concentration in erythrocyte and plasma was observed in NSP and NSO groups. There was a significant increase of total plasma antioxidant status (TAS) (p>0.05). NSP and NSO groups also showed significant reduction of serum alanine aminotransferase (ALT) and creatinine concentrations (p<0.05). Plaque formation was significantly inhibited in the aorta, and the tunica intima to tunica media ratio was significantly decreased (p<0.05). In conclusion, this study indicates that the seed of Nigella sativa cultivated in Yemen and its oil contain several nutrients and antioxidants with potential health values such as hypocholesterolemic effect, antioxidant effect and anti atherogenic effect.